Clinical Manifestation and Nursing Care Challenges of Neurogenic Bowel Disorder in Closed-Intertrochanteric Fracture Dextra an a 58-Year-Old Female with T2dm And Atelectasis-Tuberculosis: a Case Report - Rina Anggraeni; Tuti Pahria; Chandra Isabella Hostanida Purba (Universitas Malahayati, 2026)
ABSTRACT Intertrochanteric fractures, characterized by breaks in the proximal femur outside the joint capsule, present significant rehabilitation challenges, especially in older adult with comorbidities. These fractures disrupt the attachment points for major muscles and can lead to complications if not promptly and effectively treated. This case report explores the complex clinical scenario of a 58-year-old female patient with a history of Type 2 diabetes mellitus (T2DM) and tuberculosis, who suffered a closed intertrochanteric fracture dextra. The complications were exacerbated by neurogenic bowel disorder (NBD) due to prolonged immobility. The patient presented to the emergency department with severe hip pain following a fall at home, where she had been bedridden for two weeks. During this time, she developed a grade 2 decubitus ulcer. Despite her painful condition, initial treatment was delayed, leading to severe complications. A subsequent chest X-ray revealed infiltration along with atelectasis of the left superior lobe and left pleural effusion indicative of exacerbated pulmonary tuberculosis. Diagnostic imaging also identified an obstructive ileus. Immediate surgical intervention was indicated to manage the fracture. In addition to surgical care, the patient required specialized nursing care to address her acute and chronic medical needs, including blood glucose monitoring and management of her pulmonary condition. Prior to her surgery, Swadesh massage therapy was employed, resulting in minor relief indicated by the passage of a small amount of hard, mucous-like feces. Effective management of closed intertrochanteric fractures in patients with significant comorbidities requires a multidisciplinary approach. Early surgical intervention, combined with tailored nursing care and continuous monitoring of associated complications, is crucial for restoring functionality and preventing further health deterioration. Keywords: Intertrochanteric Fracture, Neurogenic Bowel Disorder, Type 2 Diabetes Mellitus, Pulmonary Tuberculosis, Multidisciplinary Care.